180 days of problem solving for kindergarten - Hathaway, Jessica (Huntington Beach, California : Shell Education, 2017)
Help kindergarten students improve critical-thinking and reasoning skills with fun and effective daily practice activities. Focusing on one skill each week, students will learn the problem-solving process: think, plan, solve, and explain.
Cover -- Credits -- Page 3 -- Table of Contents -- Page 3 -- Introduction -- Page 4 -- How to Use this Book -- Page 12 -- Standards Correlations -- Page 13 -- Daily Practice Pages -- Page 193 -- Answer Key -- Page 203 -- Practice Page Rubric -- Page 204 -- Practice Page Item Analysis -- Page 208 -- Student Item Analysis -- Page 209 -- Problem-Solving Framework -- Page 210 -- Problem-Solving Strategies -- Page 211 -- Digital Resources -- Thank You Page.
Description based on print version record.
Print version record.
eBooks on EBSCOhost
Keywords: Mathematics -- Study and teaching (Preschool) -- United States; Mathématiques -- Étude et enseignement (Préscolaire) -- États-Unis.; Mathematics -- Study and teaching (Preschool); United States